2004
DOI: 10.1029/2003jd003874
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive laboratory measurements of biomass‐burning emissions: 2. First intercomparison of open‐path FTIR, PTR‐MS, and GC‐MS/FID/ECD

Abstract: [1] Oxygenated volatile organic compounds (OVOC) can dominate atmospheric organic chemistry, but they are difficult to measure reliably at low levels in complex mixtures. Several techniques that have been used to speciate nonmethane organic compounds (NMOC) including OVOC were codeployed/intercompared in well-mixed smoke generated by 47 fires in the U.S. Department of Agriculture Forest Service Fire Sciences Combustion Facility. The agreement between proton transfer reaction mass spectrometry (PTR-MS) and open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
185
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(197 citation statements)
references
References 54 publications
9
185
0
Order By: Relevance
“…Several studies reported the humidity dependence of PTR-MS detection using comparison with other techniques. Generally, their results suggested a significant (a factor of 3 to 5) underestimate of HCHO concentrations by PTR-MS which can be improved by taking into account reaction R1a (Christian et al, 2004;Karl et al, 2003;Steinbacher et al, 2004). Good agreement was observed between HCHO concentrations measured by a specially modified PTR-MS (i.e.…”
Section: Introductionmentioning
confidence: 54%
“…Several studies reported the humidity dependence of PTR-MS detection using comparison with other techniques. Generally, their results suggested a significant (a factor of 3 to 5) underestimate of HCHO concentrations by PTR-MS which can be improved by taking into account reaction R1a (Christian et al, 2004;Karl et al, 2003;Steinbacher et al, 2004). Good agreement was observed between HCHO concentrations measured by a specially modified PTR-MS (i.e.…”
Section: Introductionmentioning
confidence: 54%
“…Other instrumentation can be placed in adjacent rooms with sample lines pulling from ports at the sampling platform. Previous studies concluded that the temperature and mixing 20 ratios are consistent across the width of the stack at the height of the platform, confirming well-mixed emissions that can be monitored by a number of different sample lines throughout the fire (Christian et al, 2004).…”
mentioning
confidence: 68%
“…The canister samples were 24 h samples with constant flow, while PTR-MS detected a total group of 17 different species with a 30 s cycle. From previous studies on comparison between the PTR-MS and the GC-MSD/FID/ECD, the slope for toluene ranged 0.52-1.18, and the slope for C 2 -benzenes ranged 0.58-3.20 (Kato et al, 2004;Christian et al, 2004;de Gouw et al, 2003;Warneke et al, 2001), so PTR-MS and offline GC-MSD/FID/ECD analysis were comparable for aromatic hydrocarbon measurements in this study.…”
Section: Ptr-ms Vs Offline Gc-msd/fid/ecdmentioning
confidence: 96%